The Role of Peer Feedback in Improving Speaking Skills During Classroom Presentations - Isnani, Shinta; Hapsari, Christianti Tri (Journal of English Language and Education, 2026)
Speaking skills remain a challenging aspect of English as a Foreign Language (EFL) learning, particularly in classroom presentations. Due to limited time for individualized teacher feedback, peer feedback has been adopted as an alternative strategy. This qualitative descriptive study investigates EFL students’ perceptions of peer feedback in improving speaking skills and identifies challenges in its implementation. Data were collected through an open-ended questionnaire administered to 27 third-semester undergraduate EFL students at an Indonesian university and analyzed thematically based on Naeem et al. (2023) and Topping’s (2009) peer assessment theory. The findings reveal that peer feedback supports cognitive development, social interaction, and improvements in fluency, pronunciation, vocabulary, and grammatical awareness, while also enhancing teachers’ time efficiency. However, challenges related to feedback accuracy, students’ confidence, and social discomfort persist. Overall, peer feedback is effective when supported by clear guidelines and teacher supervision.